Towards a globalized scholarship of comparative religion - Hashi, Abdurezak Abdulahi (2009)
In this era of globalization, people of different faiths and cultures are living together side-by-side and interactively corresponding to each other by means of cultural, economic and diplomatic relations. In this globalized environment where “no man is an island” mutual understanding and peaceful co-existence are necessary and inevitable. However, as noted by the contemporary Christian theologian Hans Kung (1992), there could be no peace among the nations, without peace among the religions; no peace among the religions without dialogue between the religions; no dialogue between the religions without investigation of the foundations of the religions. Nonetheless, while we acknowledge that it is extremely important to investigate and study the roots of other religions, the question arises what type of scholarship should be employed to study religious faiths? This is because, polemical and argumentative approaches as well as the atheistic schemes of studying religious faiths are counterproductive and generate only mistrust between religious communities and the researcher. Hence, objective and neutral scholarship of comparative religion which transcends subjective judgments and apologetics in the study of other religious teachings is needed. Though some scholars are skeptical about having independently authoritative and neutral ‘principles’ to which we can refer when studying religious faiths, this paper argues that there are independently methodological principles and common standards of reasoning based on which religions could be evaluated and understood objectively. While stressing for the need of globalized scholarship of comparative religion, through analytical and comparative methods, this paper aims to offer some evaluative remarks on the available schemes and approaches of studying religion, and then attempts to provide some thoughtful reflections on independently methodological principles and common standards of reasoning through which global religions could be understood objectively.